Sustainable Development Goals: A cluster analysis of worldwide countries - Caglar, Mehmet; Gurler, Cem (SPRINGER, 2022)
In 2015, the United Nations introduced the 2030 Agenda, which sets out Sustainable Development Goals (SDGs) for building a sustainable future. The main objective of this study is to classify worldwide countries in terms of Sustainable Development Goals progress in order to understand key implementation challenges, define the gaps between countries and identify priorities for action. 110 countries were included in the analysis. The SDG progress data used in the data analysis phase were gathered from the Sustainable Development Report 2019. To classify countries, the K-Means method, which is a non-hierarchical cluster analysis technique, was used. After constructing homogeneous groups of countries, each cluster was examined based on the socioeconomic and politico-cultural structure of the countries. The results of the cluster analysis show that the countries can be classified into 5 clusters. The countries in each cluster have substantially similar characteristics, not only in terms of progress on the SDGs, but also in terms of socioeconomic and politico-cultural structure. In general, the clusters with a more advanced socioeconomic structure and a better politico-cultural structure tend to have superior SDGs progress. Socioeconomic and politico-cultural indicators are positively related to most of the SDGs indices. This study provides crucial guidance to identify each country's achievements, challenges, needs, strengths and weaknesses in terms of progress on the SDGs. In addition, the empirical results of the study also show the importance of the superior socioeconomic and politico-cultural structure in reaching SDGs.
Keywords: Sustainable development; Sustainable Development Goals; Cluster analysis; Socioeconomic structure; Politico-cultural structure; ECONOMIC-GROWTH; EDUCATIONAL-ATTAINMENT; CONSUMPTION; SDGS; GOVERNANCE; INDICATORS; HYPOTHESIS; PROGRESS; ACHIEVE; MODELS; Science & Technology - Other Topics; Environmental Sciences & Ecology